Sofinicline: a novel nicotinic acetylcholine receptor agonist in the treatment of attention-deficit/hyperactivity disorder. (August 2014) - Fleisher, Carl; McGough, James
<x xml:space="preserve">Abstract</x> Introduction: Psychostimulants are first-line treatments for attention-deficit/hyperactivity disorder (ADHD), but their tolerability profiles and individual response variability fuel a continuing search for alternative medications. The observation that nicotinic agents improve cognition has led pharmaceutical companies to explore the potential utility of agonists of the nicotinic acetylcholine receptor (nAChR) system for ADHD treatments. Areas covered: This article reviews Phase I and Phase II trials of <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=sofinicline&logicalOpe1=OR&field2=articletitle&text2=sofinicline&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">sofinicline (ABT-894), an agonist of the nAChR α4β2 subtype, as a potential non-stimulant treatment for ADHD. This includes one Phase II trial that compared sofinicline with atomoxetine, a noradrenergic reuptake inhibitor currently approved as a non-stimulant ADHD treatment. This article also reviews the chemistry, pharmacodynamics and pharmacokinetics of sofinicline. Expert opinion: Sofinicline appears to be well tolerated and showing efficacy similar to that of atomoxetine. Although the number of patients studied to date is small, further evaluation of sofinicline in Phase II, and possibly Phase III, trials appears to be warranted. Additional studies are needed to explore the efficacy and tolerability of sofinicline with respect to: i) optimal dosing; ii) its use in combination with other medications for ADHD; and iii) its use in children and adolescents, who more commonly experience adverse effects when taking psychostimulant medications.